2007
DOI: 10.1007/s11695-008-9422-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Complications after Bariatric Surgery using Obesity-Related Co-morbidities

Abstract: Patients who exhibit multiple obesity-related co-morbidities prior to bariatric surgery are at significantly elevated risk of post-surgery complications and merit closer monitoring by health care professionals after bariatric surgery. Limitations of this study include nonexperimental data and an unknown degree of under-reporting of pre-surgery co-morbidities in claims data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
0
14
3
1
Order By: Relevance
“…54 The two comorbidities most predictive of postoperative complications were sleep apnea and gastroesophageal reflux disease; others included diabetes, hyperlipidemia, and hypertension. A study by Cawley and colleagues found that preexisting obesity-related comorbidities were significantly associated with the likelihood of developing certain complications after bariatric surgery.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 The two comorbidities most predictive of postoperative complications were sleep apnea and gastroesophageal reflux disease; others included diabetes, hyperlipidemia, and hypertension. A study by Cawley and colleagues found that preexisting obesity-related comorbidities were significantly associated with the likelihood of developing certain complications after bariatric surgery.…”
Section: Complicationsmentioning
confidence: 99%
“…55 Symptoms, which can arise 15 minutes to two hours after eating and generally last about 30 minutes, may include tachycardia, dizziness, sweating, nausea, vomiting, bloating, abdominal cramping, and diarrhea. 54 Cholelithiasis. Dumping syndrome occurs more often with RYGB than with BPD-DS, probably because the latter procedure preserves more of the stomach, including the pyloric valve.…”
Section: Complicationsmentioning
confidence: 99%
“…Certain surgical complications, such as band slippage[15, 16], have been indicated in increasing the risk of GERD following surgery. Additionally, patients with GERD prior to surgery may be more likely to experience surgical complications than patients with other obesity-related co-morbidities[17]. The relationship between surgical complications and GERD medication use may therefore be bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical technique in this trial involved incision of the gastrohepatic ligament "lateral to the left gastric artery," with an opening made in the lesser omentum made along the lesser curvature; it is not clear how much of the lesser omentum was transected in this trial. A review of private health insurance claims in a series of 1,760 bariatric patients found a 15.7% incidence of dumping [26]; surgical details from this database were not available.…”
Section: Discussionmentioning
confidence: 99%